Association of combined genetic variations in SOD3, GPX3, PON1, and GSTT1 with hypertension and severity of coronary artery disease - Decharatchakul, Nisa; Settasatian, Chatri; Settasatian, Nongnuch; Komanasin, Nantarat; Kukongviriyapan, Upa; Intharapetch, Pongsak; Senthong, Vichai; Sawanyawisuth, Kittisak (Heart and vessels, 2020)
Oxidative stress plays a critical role in the pathophysiology of hypertension (HT) and the progression of atherosclerotic coronary artery disease (CAD). Genetic variations in superoxide dismutase ( SOD ), glutathione peroxidase 3 ( GPX3 ), paraoxonase 1 ( PON1 ) and glutathione S -transferase theta 1 ( GSTT1 ) may modulate their gene functions, affecting protein functions. These changes could have an impact on the pathogenesis of HT and progression of CAD. The present study investigated the associations of individual and combined antioxidant-related gene polymorphisms with the incidence of HT and severity of CAD. Two study populations were enrolled. The HT-associated study comprised 735 control and 735 hypertensive subjects (mean age 59.3 ± 9.0 years), matched for age and sex. The CAD study, hospital-based subjects (mean age 62.1 ± 9.5 years), included 279 CAD patients and 165 non-CAD subjects. Gene polymorphisms were identified in genomic DNA using polymerase chain reaction (PCR)-based technique. Genetic variations were assessed for their associations with HT and severity of CAD. Antioxidant gene variants, SOD3 rs2536512-GG, GPX3 rs3828599-GG, PON1 rs705379-TT, and GSTT1 −/− and +/− , were independently associated with the incidence of HT. A combination of four HT-associated genotypes, as a genetic risk score (GRS), revealed an association of GRS 5 and GRS ≥ 6 with increased susceptibility to HT and CAD, and further with multivessel coronary atherosclerosis (multivessel CAD) compared with GRS 0–2 [respective ORs(95% CI) for GRS ≥ 6 = 2.37 (1.46–3.85), 3.26 (1.29–8.25), and 4.36 (1.36–14.0)]. Combined polymorphisms in these four antioxidant-related genes were associated with the incidences of HT and CAD, and with the severity of coronary atherosclerosis.